Modulations of the South China Sea Ocean Circulation by the Summer Monsoon Intraseasonal Oscillation Inferred from Satellite Observations - Zhiyuan Hu; Keiwei Lyu; Jianyu Hu (Remote Sensing, 2024)
The South China Sea (SCS) displays remarkable responses and feedback to the summer monsoon intraseasonal oscillation (ISO). This study investigates how the SCS summer ocean circulation responds to the monsoon ISO based on weekly satellite data. In summer, the largest amplitudes for intraseasonal (30–90 days) sea surface height variations in the SCS occur around the northeastward offshore current off southeast Vietnam between a north–south eddy dipole. Our results show that such strong intraseasonal sea surface height variations are mainly caused by the alternate enhancement of the two eddies of the eddy dipole. Specifically, in response to the intraseasonal intensification of southwesterly winds, the northern cyclonic eddy of the eddy dipole strengthens within 1–2 weeks, and its southern boundary tends to be more southerly. Afterwards, as the wind-driven southern anticyclonic gyre spins up, the southern anticyclonic eddy gradually intensifies and expands its northern boundary northward, while the northern cyclonic eddy weakens and retreats northward. Besides the local wind forcing, westward propagations of the eastern boundary-originated sea surface height anomalies, which exhibit latitude-dependent features that are consistent with the linear Rossby wave theory, play an important role in ocean dynamical adjustments to the monsoon ISO, especially in the southern SCS. Case studies further confirm our findings and indicate that understanding this wind-driven process makes the ocean more predictable on short-term timescales.